Telang Product Innovation Training in an Effort to Increase Income During the Pandemic In Sukolelo Prigen Hamlet: Pelatihan Inovasi Produk Telang Dalam Upaya Peningkatan Income Pada Masa Pandemi Di Dusun Sukolelo Prigen - Farera, Jihan Nada; Noviananda, Rizki; Fitriandini, Yolanda Wahyu (Universitas Muhammadiyah Sidoarjo, 2022)
This activity aims to increase product innovation in the processing of telang flowers in the ASMANTOGA group in Sukolelo Hamlet. This activity also has the aim of increasing income during the covid 19 pandemic. Based on observations that have been made, there are problems with decreasing product sales during the covid 19 pandemic. Therefore, the KKN group of 67 Universitas Muhammadiyah Sidoarjo team innovated a product made from telang flower. This implementation method is carried out by the method of socialization and training. Based on the results of the activities that have been carried out, the results of product innovations from telang flower in the form of telang candy and packaging innovations are achieved to increase consumer attractiveness.